Robust Constant Exponent Coefficient Fixed-Time Control Based on Finite-Time Extended Sliding Mode Observer of Permanent Magnet Synchronous Motors - Varin Cholahan; Napasool Wongvanich; Worapong Tangsrirat (My University, 2023)
This paper presents the Robust Constant Exponent Coefficient Fixed-Time Control (CECFSMC), an innovative control technique for precisely regulating the speed of a permanent magnet synchronous motor (PMSM) by utilizing fixed-time stability with constant exponent coefficients to provide not only faster convergence but also in a specific period of time. The effect of chattering is also lessened. To ensure that the designed controller produces the desired performance under bounded disturbances, a finite-time extended sliding-mode observer (ESMO) is also designed to estimate the PMSM velocity while also estimating lumped load disturbances. The considered PMSM is the surface-mounted PMSM. Finally, a numerical simulation with PMSM drive shows good robustness against load disturbances, better convergence, and a reaching time of less than 2 s, thereby demonstrating that the proposed fixed-time constant exponent coefficient offers good performance and is much simpler than the conventional finite-time method.
Keywords: Robustness; Constant (computer programming); Exponent; Observer (physics); Synchronous motor; Sensorless Control of Electric Motors